Preparo do solo, inoculação de sementes e doses de nitrogênio em cobertura no feijoeiro comum de inverno irrigado - Arf, Orivaldo [UNESP]; Da Silva, Flávia Catiuci Robim [UNESP]; Arf, Marcelo Valentini [UNESP]; Rodrigues, Ricardo Antônio Ferreira [UNESP]; De Sá, Marco Eustáquio [UNESP]; Buzetti, Salatiér [UNESP] (My University, 2011)
Common bean is a demanding plant in nutrients, mainly in relation to nitrogen. The adoption of a management system that improves the soil conditions, associated to the appropriate nitrogen supply can be very important to increase the plant efficiency in the use of the available resources. This study aimed to evaluate different combinations of soil management, seed inoculation and nitrogen doses in the growth and yield of irrigated common bean plant in winter period. The experiment was conducted in Selvíria county (MS) in years of 2006 and 2007. A randomized completely blocks design in a factorial scheme 3 x 2 x 4, constituted by three soil management (chisel ploughing + leveling disk, heavy disk + leveling disk, and no till), seed inoculation with Rhizobium tropici ( with or without inoculation) and nitrogen doses at sidedressing on stage V4-5 (zero, 60, 120 and 180 kg ha-1), with four repetitions, was used. The soil management with chisel ploughing, heavy disk, or no till, and the use of seed inoculation with Rhizobium tropici does not interfere in the irrigated common bean yield; the nitrogen fertilization at sidedressing provides increment above 17% at dose of 180 kg ha-1 of nitrogen in relation to control.
Soil management, seed inoculation and nitrogen application at sidedressing on common bean in winter
Keywords: Chisel ploughing; Heavy disk; No till; Phaseolus vulgaris L.; Rhizobium tropici